Autobiography of a Malaysian Indian woman: From Shore to Shore - Omar, Haslina (Asia Pacific Institute of Advanced Research, 2016)
This paper is part of a series of studies done to perpetuate interest and attention towards multiethnic Malaysian women’s autobiographies, not only for their literary value, but also as potential sources of alternative perspectives on Malaysian history (Haslina, 2013). The notion that Malaysian women of all ethnic backgrounds live in a gendered world, in which women are assigned to the home and passive and uninvolved in the country’s political changes may be the reason why there seems to be an attitude of inattentiveness or an indifference towards autobiographies by Malaysian women. Women’s life narratives are representations of their lived experiences written and published with the purpose of sharing it with others. However, only a small number of Malaysian women have published autobiographies; rather than being evidence of insignificance, according to Lim, the number points to “the unfavourable conditions under which they wrote” (1994). This paper attempts to draw insights from life writing that can greatly enhance our historical understanding of the development of women in Malaysia and also for its literary significance. It seeks to answer a call for the creation of a new practice of reading women’s autobiographies, especially those by women from multiethnic communities (Smith &Watson, 1992). This paper reads into a Malaysian autobiography entitled From Shore to Shore by Muthammal Palanisamy (2002) in an attempt to erase the notion that Malaysian women’s life narratives are trivial, but instead allow readers to make clearer connections with the literary, historical and social cultural viewpoints.